Penguatan Usaha Mikro Kecil Menengah (UMKM) pada Starra Kitchen Kediri Untuk Meningkatkan Kualitas Produk dan Layanan - Mubaroroh, Arina; Martha, Emilya; Afriyanti , Siska; Rahmah, Miladia; Lomansari, Dwi; Syecha, Aulia Himatus; Auliya, Masriatul Dwi (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
Strengthening Micro, Small and Medium Enterprises (MSMEs) is a strategic step in improving the quality of products and services, especially at Starra Kitchen Kediri. Starra Kitchen, as one of the MSMEs operating in the culinary sector, faces challenges in the form of intense market competition and the need for innovation to maintain competitiveness. This community service activity aims to increase management capacity, product quality and customer service through an Asset-Based Community Development (ABCD) approach. This method involves identifying local potential and assets owned by Starra Kitchen to develop sustainable strengthening strategies. Implementation of activities includes business management training, product innovation, and improving service skills based on customer needs. The results of the activities showed significant improvements in product quality, service efficiency and customer satisfaction. By utilizing existing potential, Starra Kitchen has succeeded in increasing its competitiveness, while also having a positive impact on the development of MSMEs in Kediri.